Research of using open double t beams for spans in floating bridges - Gorbatiuk, YU. M.; Soldatov, K. I.; Papko, M. S. (Science and Transport Progress, 2014)
Purpose. The publication presents the results of calculations of spans for floating bridges with open double T beams. The purpose of research is to analyze the suitability of spans from open double T beams for floating bridges with minimum weight under loads, which is provided by standards for modern floating bridges designing. Methodology. Comparative method, analytical calculation methods (influence lines methodology), strength calculations, endurance, maximum shear stress are used in this paper. Findings. Current loads for bridges calculations are 75% more than those, for which the spans of floating bridge from NZhM-56 property are designed. The use of open double T beams that is formed with double T beam no. 70 (the height of the open one is 104 cm) reduces the cross sectional area in a weakened spot, but virtually it does not influence the strength and durability of the material. The use of open double T beams for spans of floating bridges saves up to 22 % of metal that means one in five spans will made of saved metal. Savings on each spans, such as CRP, will be 33.6 - 263 thous. grn. (considering the price of 1 ton of final product 29 thous. grn.). Originality. Research allows making next step in material saving and use of open double T beams for spans in the whole. Practical value. The obtained results give us possibility to make a number of conclusions that allow us to become more familiar and more practical with the use of open double T beams for spans of floating bridges.